2006
DOI: 10.1111/j.1439-037x.2006.00235.x
|View full text |Cite
|
Sign up to set email alerts
|

Development of Sequence‐characterized DNA Markers Linked to Temperature Insensitivity for Fruit Production in Longan (Dimocarpus longan Lour.) Cultivars

Abstract: In this paper, we characterize a temperature dependence in longan (Dimocarpus longan Lour.) cultivars using the high annealing temperature random-amplified polymorphic DNA (HAT-RAPD) methodology. This form of genomic analysis allows a random sampling of the complete genome to provide information about phenotypic traits of interest. Using a set of 18 unique decamer primers, polymorphic bands ranging from 100 to 2500 bp were examined for 14 longan varieties from which banding patterns of interest were selected f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
4
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…Previous studies of off-season flowering in other fruit trees have reported the use of chemical reagents to induce off-season flowering, such as potassium chlorate (KClO 3 ), hydrogen peroxide (H 2 O 2 ), and nitric oxide (NO) in longan (Cutler et al 2007;Manochai et al 2005;Subhadrabandhu and Yapwattanaphun 2001;Zhang et al 2016), and paclobutrazol in mango (Husen et al 2021;Nartvaranant et al 2000). Furthermore, the application of external hormones (Astiari et al 2021), light intensity (Nguyen et al 2020), or physical stresses (Kulkarni 1986) can stimulate off-season flowering as well.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies of off-season flowering in other fruit trees have reported the use of chemical reagents to induce off-season flowering, such as potassium chlorate (KClO 3 ), hydrogen peroxide (H 2 O 2 ), and nitric oxide (NO) in longan (Cutler et al 2007;Manochai et al 2005;Subhadrabandhu and Yapwattanaphun 2001;Zhang et al 2016), and paclobutrazol in mango (Husen et al 2021;Nartvaranant et al 2000). Furthermore, the application of external hormones (Astiari et al 2021), light intensity (Nguyen et al 2020), or physical stresses (Kulkarni 1986) can stimulate off-season flowering as well.…”
Section: Introductionmentioning
confidence: 99%
“…By understanding the mechanism of action inducing this out of season fruit production, insight into other tropical fruits may lead to further advances making other fruits such as Lychee or Longong similarly available. Recently, molecular markers linked to the temperature independence for fruit production phenotype in both Lychee [9] and Longan [10] have been reported. In spinach, potassium chlorate and 5-azacytidine-treated spinach both develop an early flowering phenotype [11] , indicating that potassium chlorate might also play a similar role to 5azacytidine [12] .…”
Section: Introductionmentioning
confidence: 99%
“…One such method uses sequence characterized amplified region (SCAR) markers [14] to amplify unique regions in different varieties or species. Such a methodology has been successfully demonstrated in a characterization of the temperature dependence of lychee cultivars [15], longan cultivars [16], as well as in the cut flower Curcuma [17]. By extracting a single genetically defined loci, the presence or absence of an amplified band can be used as a distinguishing unique character of that species or clade of species.…”
Section: Introductionmentioning
confidence: 99%